STUDENTS MOTIVATION IN E-LEARNING TROUGH GOOGLE CLASSROOM APPLICATION ON WRITING SKILL AT EIGHT GRADE OF SMP N 1 KALIWUNGU - Ineke Yustina Kristin; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2022)
The research was aimed: 1) To To analyze the students motivation in e-learninng troughgoogle classroom on writting skill at eight grade SMP N 1 Kaliwungu, Semarang and, 2) Toanalyze the problem on students of motivation intrinsic and extrinsic motivation in e-learning atstudent’s eight grade of SMP N 1 Kaliwungu, Semarang. This research was conducted on August2021, . The researcher took 33 students 8A grade of SMP N 1 Kaliwungu as the subject. A casestudy qualitative research was used in this study. To collect the data, the researcher usedquestionnaire and interview. The questionnaire above used the document and share to the studentsafter interview with the teacher face-to-face. To validity data, the researcher used datatriangulation. To analyzed data used qualitative interactive: data reduction, data, display,conclucion drawing/verification. The result of the research show that: 1) the students’ motivationintrinsic in E-learning English used Google Classroom was the students easily understood thematerial and it was not too difficult. The students’ motivation extrinsic in E-learning English useGoogle Classroom application was the students were less interested in students because they weremore interested in other subjects than English. 2) The students problems in e-learning troughgoogle classroom on writing skill, they were very enthusiastic about offline learning than elearningwith Google Classroom application for distance learning especially on writing skillKeywords : Student Motivation, E-Learning,Google Classroom,Writing skill